A critical review of knowledge management frameworks - Wong, Kuan Yew (Inderscience Publisher, 2005)
The prominence and importance of Knowledge Management (KM) has been increasingly recognised in the academic and business arena. As such, many researchers and practitioners have developed various frameworks and other relevant approaches to help the emergence of KM into practice. However, most of the existing frameworks appear to have been derived from the experiences and considerations of large organisations, rather than small firms. Approaches that work in large companies may not be suitable for small ones. The first part of the paper is devoted to understanding the characteristics of small businesses, as well as their associated advantages and disadvantages in implementing KM. This provides the fundamental basis for justifying the suitability of the frameworks when applied to their environment. Following this, various frameworks that are found in the literature are reviewed. It is shown that most of the frameworks are not well adapted to the needs and characteristics of small businesses. Improvements are indeed needed to help them in their journey to implement KM. The paper culminates with some future research directions on the development of a more suitable framework to meet their needs.